Local Values and Judges’ Legal Discretion in Islamic Court of Makassar: the Case of “Dispensasi Nikah” - Mustofa, Kholifatun Nur (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2022)
Abstract: This paper examines the legal considerations used by judges in the case of marriage dispensation at the Makassar Religious Court. This paper focuses on two things, first, the judge's consideration in deciding the marriage dispensation case, while the second focus is on the age of youngest couple who applied for a marriage dispensation. The marriage dispensation decision at the Makassar Religious Court is used as the primary source, while the secondary sources are collected from interviews and scientific works related to the topic of this research. Legal pluralism is applied as an approach to determine which law is more dominant in granting marriage dispensation in Makassar. The results revealed that majority of judges use customary law as a legal consideration in granting marriage dispensation cases at the Court. The judge used customary law as a consideration to granting a marriage dispensation application. It is reported that the youngest age in the marriage dispensation was 13 years for women and 14 years for men. The author found that 13 of the 16 cases of marriage dispensation stated that the child of the applicant who filed the marriage dispensation case was not pregnant. Abstrak: Paper ini mengkaji tentang pertimbangan hukum yang digunakan oleh hakim dalam memutuskan perkara dispensasi nikah di Pengadilan Agama Makassar. Tulisan ini berfokus pada dua hal, pertama, pertimbangan yang digunakan hakim dalam memutuskan perkara dispensasi nikah. Kedua fokus pada berapa usia pasangan termuda yang mengajukan dispensasi nikah. Putusan dispensasi nikah di Pengadilan Agama Makassar penulis gunakan sebagai sumber primer, sedangkan sumber sekunder penulis dapatkan dari wawancara dan karya ilmiah yang berkaitan dengan topik penelitian ini. Pluralisme hukum diterapkan sebagai pendekatan untuk menentukan hukum mana yang lebih dominan dalam pemberian dispensasi perkawinanPengadilan Agama Makassar. Hasil penelitian menunjukkan bahwa mayoritas hakim menggunakan hukum adat sebagai pertimbangan hukum dalam mengabulkan perkara dispensasi nikah di Pengadilan. Hakim menggunakan hukum adat sebagai pertimbangan untuk mengabulkan permohonan dispensasi nikah. Penelitian ini mengungkapkan bahwa usia termuda dalam dispensasi perkawinan adalah 13 tahun untuk perempuan dan 14 tahun untuk laki-laki. Penulis menemukan bahwa 13 dari 16 kasus dispensasi nikah menyatakan bahwa anak pemohon yang mengajukan dispensasi nikah tidak hamil.